Analysis of Factors Relating to Pregnant Women's Knowledge About Triple Elimination at Andalas Health Center, Padang City - Aisyah, Siti; Basyir, Vaulinne ,; Wydya, Satya; Sriyanti, Roza; Silviam, Nelmi; Ali, Hirowati (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Pregnant mother is group woman vulnerable at risk transmit Human Immunodeficiency Virus (HIV), Hepatitis B, and Syphilis to fetus . Effort disconnect transmission of HIV, Syphilis , and Hepatitis B from Mother pregnant to the fetus is one of them with inspection triple elimination . Objective study For know related factors with knowledge Mother pregnant about triple elimination at the Community Health Center Andalas. Study This is study quantitative with analytical and observation methods design cross sectional carried out in the Puskesmas area Andalas . Sample study totaling 98 mothers pregnant taken with method consecutive sampling. Primary data collection uses questionnaire and analyzed with chi square and regression tests logistics. Research result univariate part big own low education , no work , supportive husband , support power poor health , and exposure insufficient information . Analysis bivariate using the chi square test there is significant relationship between education ( p-value 0.011), employment ( p-value 0.038), support power health ( p-value 0.020), exposure information ( p-value 0.039) with knowledge Mother pregnant about triple elimination . No there is connection support husband ( p-value 0.453) with knowledge Mother pregnant about triple elimination . Analysis Multivariate using regression testing logistics obtained related factors with knowledge Mother pregnant about triple elimination is exposure information and education , the most dominant factors is education ( p-value 0.009). Conclusions of educational Research identified as factor related dominant to knowledge Mother pregnant about triple elimination. Expected Public health centers in Andalas do cooperate cross sector to improve knowledge Mother about triple elimination as an effort promotional and preventive in prevent HIV, Syphilis, and Hepatitis B.